27 The effectiveness of a targeted protein education intervention to increase protein intake in patients with coronary heart disease and low protein intake: A pilot randomised controlled trial. (20th December 2022) - James, Emily
Abstract : Background: Low protein intake is prevalent in, and detrimental to, patients with coronary heart disease (CHD). We have shown that protein education in UK cardiac rehabilitation (CR) needs improvement. Evidence-based targeted protein education may increase protein intake in patients with CHD. Aim: To identify whether targeted education increases protein intake in patients with CHD and low protein intake, compared with standard CR dietary education. Methods: Patients referred to CR with CHD (≥50 years) will complete a three-day food diary, five repetition sit-to-stand test and three questionnaires (Physical Activity Vital Signs, SARC-F, and a researcher-developed nutrition knowledge questionnaire). Stature, mass, waist circumference and medical history will be assessed. Patients with low protein intake (≤1.2 g/kg/day) will be randomised to receive a pre-recorded education session, either promoting increased protein intake and improved quality of protein sources (intervention) or reiterating standard CR dietary education (control). At 6-weeks and 12-weeks, patients will repeat the food diary, sit-to-stand test, questionnaires, and anthropometric measures. Results: Preliminary findings will be presented at the conference. Mean difference with 95% confidence intervals and effect sizes will be reported between groups for primary (change in protein intake) and secondary (sit to stand time, questionnaire scores, change in waist circumference) outcomes at study timepoints. Significance testing will not be performed due to inadequate statistical power. Pilot studies require n ≥24; we aim to recruit 30 participants (15 per group) to account for an estimated 20% attrition at 12-weeks, between October 2021 and September 2023. Conclusion: Insufficient protein intake contributes to muscle mass loss and impaired healing. Dietary education in CR traditionally focuses on weight loss and lipid management over protein intake. If protein intake can be increased using targeted education sessions, this method may be more easily and cost-effectively integrated into standard CR, compared to alternative dietary interventions such as supplementation.